Selection of components of the compositional protein-carbohydrate mixture to improve the quality of the chopped semi-finished products - Honcharenko, Taisa; Topchiy, Oksana (My University, 2019)
Meat is one of the most significant and nutritious foods available for the masses, which helps to satisfy most of the needs of the body. It has is a good source of proteins, zinc, iron, selenium, and phosphorus followed by vitamin A and B-complex vitamins. The modern production of meat products develops in the direction of expanding assortment of production, combining and optimizing the component composition in order to increase the nutritional value, substances by including in the recipe of the functional ingredients. The article presents the results of the study of qualitative indicators of animal origin protein preparations and protein-carbohydrate composition based on beef collagen protein and mixture of oilseed cultures flour for use in the recipe of chopped semi-finished products to improve their biological value. The aim of the study was to determine and compare the qualitative indicators of animal origin protein preparations, to create a compositional proteincarbohydrate mixture based on the selected animal protein and flour of oilseed cultures, to study its functional-technological properties in view of being used in the recipe of the chopped semi-finished products. Based on the study and comparative analysis of qualitative indicators of animal origin protein preparations, the use of Helios-11 beef collagen protein in the composition of a proteincarbohydrate composition was selected and substantiated. Ratios of protein and mixture of oilseed cultures flour (1: 4) have been determined, which create the most favorable conditions for the correction of meat systems by their functional-technological properties, providing an acceptable and stable level of emulsifying and water-binding properties. М'ясо є одним з найбільш значущих і поживних продуктів, доступних масам допомагає задовольнити більшість потреб організму. Він є хорошим джерелом білків, цинку, заліза, селену, і фосфор, а потім вітамін А і вітаміни B-комплексу. Сучасне виробництво м'яса продукції розвивається в напрямку розширення асортименту продукції, комбінування та оптимізації компонентний склад з метою підвищення харчової цінності, речовин шляхом включення в рецепт функціональних інгредієнтів. У статті наведено результати дослідження якісних показники білкових препаратів тваринного походження та білково-вуглеводного складу на основі яловичини колагеновий білок і суміш борошна олійних культур для використання в рецептурі січених напівфабрикатів продуктів для підвищення їх біологічної цінності. Метою дослідження було визначити та порівняти якісні показники білкових препаратів тваринного походження, для створення білково-вуглеводного складу суміші на основі виділеного тваринного білка та борошна олійних культур, вивчити її функціонально-технологічні властивості з урахуванням використання в рецептурі січених напівфабрикатів продуктів. На основі вивчення та порівняльного аналізу якісних показників тваринного походження білкових препаратів, використання протеїну яловичого колагену Геліос-11 у складі білка вуглеводного вибрано та обґрунтовано склад. Співвідношення протеїну та суміші олійних культур визначено культури борошна (1:4), які створюють найбільш сприятливі умови для в корекція м'ясних систем за їх функціонально-технологічними властивостями, що забезпечують прийнятну та стабільний рівень емульгувальних і водозв'язуючих властивостей.
Keywords: кафедра технології м’яса і м’ясних продуктів; oilseed cultures flour; meat products; animal proteins; борошно олійних культур; м'ясні продукти; тваринні білки